Der melodische Leitfähigkeitsprüfer – low cost mit großer Leistung. Issue 1 (15th January 2018) - Bee, Ulrich; Jansen, David
Translation abstract: The Melodic Conductivity Tester (LF‐Prüfer) is not only capable to qualitatively check whether a material is electrically conductive, but also allows quantitative statements. Although it is not possible to measure the exact conductivity as in a commercial conductometer, different auditory characteristics are, however, perceptible depending on the conductivity. Even the electrical conductivity of deionized water can be demonstrated.